2016
DOI: 10.5539/ijel.v6n3p208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Professional Challenges Faced by Iranian Teachers of English

Abstract: The objective of the present study is to understand professional challenges faced by Iranian high school teachers of English through exploring their viewpoints. To this end, it benefits from both qualitative and quantitative modes of inquiry. First, grounded theory method was used to conduct some interviews with 20 EFL teachers and members of educational groups in the Education Organization, Shiraz, Iran. After coding the obtained data, a number of concepts and categories were identified and a model was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…As for the second question, which seeks to the effect of teachers' gender on their perspective toward teaching difficulties. The finding is in line with studies' results of (Razmjoo & Mavaddat, 2016;Mahmoud, 2004) disclosed that both male and female teachers experience approximately the same level of difficulties in teaching English language, which means there is no statistically significant difference between male and female teachers' perspectives toward teaching English difficulties.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As for the second question, which seeks to the effect of teachers' gender on their perspective toward teaching difficulties. The finding is in line with studies' results of (Razmjoo & Mavaddat, 2016;Mahmoud, 2004) disclosed that both male and female teachers experience approximately the same level of difficulties in teaching English language, which means there is no statistically significant difference between male and female teachers' perspectives toward teaching English difficulties.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the main objective of the current research is to determine the most influential difficulties that face Iraqi-English teachers as they have experienced through the teaching process. Two questions were raised; the finding of the first question came to be congruent with the findings of studies conducted by (Mahmoud, 2004;Evue, 2013, Herzallah, 2011Razmjoo & Mavaddat, 2016) revealed that the scarcity of materials and facilities constitute the highest influential domain compared to the other domains that come in turn. According to these studies, which were conducted in different contexts of the Middle East, it is clear that teaching materials form a significant obstacle for English teachers not only in Iraq but also in many other places.…”
Section: Discussionmentioning
confidence: 57%
“…It is considered the most common difficulty that causes students' apathy and discouragement in EFL classrooms. Razmjoo and Mavaddat (2016) conducted a study intending to examine the viewpoints on professional challenges faced by English high school teachers in Iran. The results proved the presence of difficulties in terms of education, society, economy, and time.…”
Section: Challenges Faced By Novice Teachersmentioning
confidence: 99%
“…Therefore, attributing the existing problems to an individual factor which may play a role in students' learning is unwise. No one is to blame now because everyone, from students and their parents to the high officials in the country, has somehow a hand in creating the situation (Razmjoo & Mavaddat, 2016).…”
Section: The Role Of Teachersmentioning
confidence: 99%